An inventory of opencast mining excavations recultivated in the form of water reservoirs as an example of activities increasing the retention potential of the natural environment: a case study from Poland - Szafarczyk, Anna; Gawałkiewicz, Rafał (Geology, Geophysics and Environment, 2023)
The article presents examples of the employment of various geodetic measuring tools used for a detailed inventory of lake basins and shorelines. The measurement and analysis covered three post-mining open pit excavations recultivated as water reservoirs: two in Krakow (Bagry Wielkie and Bagry Małe) and one in Piaseczno (Piaseczno Sulphur Mine). Attention was paid to the factors that reduce the accuracy of the inventory of some flooded post-mining excavations, which determine the degree of usefulness of the morphometric data set for later analyses. According to available estimates, only about one-third of all water reservoirs in Poland have detailed geodetic documentation in the form of bathymetric maps. This documentation usually does not include water reservoirs of anthropogenic origin formed after the flooding of post-mining excavations (mines: sand, gravel, clay, limestone, sulphur, aggregates, etc.). The authors suggest the introduction of a document known as a reservoir documentation card and the creation of a database covering all anthropogenic water reservoirs. Considering the water deficit in Poland, it may be necessary to develop a detailed database of water resources in the short term.